Cultivating a dialogue with the comments of Azaola, Schritzmeyer and Thévenot - Cardoso de Oliveira, Luís Roberto (Anuário Antropológico, 2023)
The three commentators invited by Anuário Antropológico all provide intriguing and provocative readings of my text and I thank them from the outset for the attentiveness and generosity of their comments. Azaola, Schritzmeyer and Thévenot address the conceptual and ethnographic dimensions of the text in equally balanced form, albeit with different emphasises in each case.